Coherentism Discomposed: A Critique of Bonjour's the Structure of Empirical Knowledge - Haack, Susan (Theoria et Historia Scientiarum, 2007)
I think Lewis is quite right to hold that its inability to allow the relevance of experience to justification is an insuperable difficulty for coherentism. Coheren- tists, however, naturally enough, argue that the difficulty is superable. This paper is a case study of one attempt to overcome it: BonJour’s. BonJour attempts to accommodate experiential input within a coherentist framework by means of the imposition of an additional requirement, the ‘Observation Requirement’, on justification. This, however, turns out to be ambiguous: on one interpretation it is compatible with coherentism but fails to guarantee experiential input; on the other, it guarantees observational input all right but sacrifices the coherentist character of the theory.